The effects of stem length and core placement on shRNA activity - Mcintyre, Glen J (BioMed Central, 2011)
BACKGROUND: Expressed short hairpin RNAs (shRNA) used in mammalian RNA interference (RNAi) are often designed around a specific short interfering RNA (siRNA) core. Whilst there are algorithms to aid siRNA design, hairpin-specific characteristics such as stem-length and siRNA core placement within the stem are not well defined. RESULTS: Using more than 91 hairpins designed against HIV-1 Tat and Vpu, we investigated the influence of both of these factors on suppressive activity, and found that stem length does not correspond with predictable changes in suppressive activity. We also detected multiple processed products for all stem lengths tested. However, the entire length of the hairpin stem was not equally processed into active products. As such, the placement of the siRNA core at the base terminus was critical for activity. CONCLUSION: We conclude that there is no fixed correlation between stem length and suppressive activity. Instead, core selection and placement likely have a greater influence on the effectiveness of shRNA-based silencing.